(untitled) (Research, Society and Development, 2023)
This work demonstrates how the technological areas help in the agility, organization of resources and handling of data in the accounting sector. The evolution of ERP software and Cloud Computing make the technological resources available to the sector infinite. The data collection method is based on an integrative literature review along the lines of essays, attenuating the concepts that permeate the relationship between software and digital accounting in the light of bibliographic sources. The results reveal that a good part of the resources are dedicated to the mining, handling and allocation of data, whether from customers or accounting itself. To handle a large amount of data, we use tools such as Business Intelligence. To store this data, we use Cloud Computing. All these tools are used to increase the company’s range of customers and organize accounting processes.